Credit shocks and the European labour market - Katalin Bodnár; Eliana Viviano; Ludmila Fadejeva; Marco Hoeberichts; Mario Izquierdo Peinado; Christophe Jadeau (European Central Bank (ECB), 2018)
More than five years after the start of the Sovereign debt crisis in Europe, its impact on labour market outcomes is not clear. This paper aims to fill this gap. We use qualitative firm-level data for 24 European countries, collected within the Wage Dynamics Network (WDN) of the ESCB. We first derive a set of indices measuring difficulties in accessing the credit market for the period 2010-13. Second, we provide a description of the relationship between credit difficulties and changes in labour input both along the extensive and the intensive margins as well as on wages. We find strong and significant correlation between credit difficulties and adjustments along both the extensive and the intensive margin. In the presence of credit market difficulties, firms cut wages by reducing the variable part of wages. This evidence suggests that credit shocks can affect not only the real economy, but also nominal variables.
Keywords: D53; E24; E44; G31; G32; 330; credit difficulties; labour input adjustment; intensive margin